2018
DOI: 10.18488/journal.8.2018.61.65.73
|View full text |Cite
|
Sign up to set email alerts
|

Personal Income Tax and Economic Growth: A Comparative Study Between China and Pakistan

Abstract: Article History

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…They found that financial development has a positive and significant effect on economic growth. Amin et al (2018) examined the effect of taxation on economic growth in China and Pakistan during the period 1986 to 2015. Applying estimation based on cointegration analysis and the ARDL model, they found that taxation positively affects long-term economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that financial development has a positive and significant effect on economic growth. Amin et al (2018) examined the effect of taxation on economic growth in China and Pakistan during the period 1986 to 2015. Applying estimation based on cointegration analysis and the ARDL model, they found that taxation positively affects long-term economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Amin et al [9] compared the relationship between personal income tax and economic growth in China and Pakistan using Granger Causality frameworks. The result showed that in Pakistan and China, PIT had a positive influence on economic growth, among others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The taxation system is an effective and powerful avenue for mobilizing a country's internal resources. The primary goal of a taxation system is to decrease income inequality, finance public goods and services in an economy, encourage effective resource allocation, and economic stability (Amin, Chen & Huang, 2018). Taxation is a fiscal policy instrument used by government of nations to generate revenue.…”
Section: Introductionmentioning
confidence: 99%
“…The survey of mutual impact of personal income tax and economic growth (Amin et al, 2018) shows the existance of long run bond between these two variables. The results present significant relation of personal income tax and economic growth in case of China and Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%